Net Migration of the Population of the United States by Age, Race and Sex, 1970-1980 - White, Michael J. ([Verlag nicht ermittelbar], 1988)
This data collection provides net migration estimates by age, race, and sex for counties of the United States. Population data are included along with absolute net migration data and net migration ratios (rates) for the period 1970-1980. Summary records for states, divisions, regions and the United States are also supplied. Several data categories are presented in the collection. Vital Statistics data tabulate births by sex and race (white and non white) for the periods 1970-1974 and 1975-1979 and deaths by race from 1970-1979 as well as adjusted total population for 1970 and 1980 by race. The Enumerated and Adjusted 1970 and 1980 Population categories offer population totals by race and sex and further subdivide these totals into 16 5-year age ranges. Net Migration Estimates and Net Migration Rates are available also, with totals by sex and race presented along with the 16 age divisions.